Tracheostomy in suspected or confirmed cases of COVID-19 - Terence Pires de Farias; Fernando Luiz Dias; José Guilherme Vartanian; Carlos Eduardo Santa Ritta Barreira; Alexandre Ferreira Oliveira; Heber Salvador de Castro Ribeiro; Paulo Henrique de Sousa Fernandes; Reitan Ribeiro; Luiz Paulo Kowalski (Brazilian Journal of Oncology)
The focus of this review is to present the consensus of head and neck surgery experts on tracheostomy during COVID-19 outbreak. Considerations about the ideal time to perform, surgical team, appropriate location, technique, and the necessary surgical equipment of the procedure were described to minimize risks of contamination of health care workers and hospital facilities.